Hybrid electromagnetic and moisture energy harvesting enabled by ionic diode films - Zhenguo Gao; Cuiqin Fang; Yuanyuan Gao; Xin Yin; Siyuan Zhang; Jian Lu; Guanglei Wu; Hongjing Wu; Bingang Xu (Nature Communications)
Abstract Wireless energy-responsive systems provide a foundational platform for powering and operating intelligent devices. However, current electronic systems relying on complex components limit their effective deployment in ambient environment and seamless integration of energy harvesting, storage, sensing, and communication. Here, we disclose a coupling effect of electromagnetic wave absorption and moist-enabled generation on carrier transportation and energy interaction regulated by ionic diode effect. As demonstration, a wireless energy interactive system is established for electromagnetic-moist coupled energy harvesting and signal transmission through highly integrated polyelectrolyte/conjugated conductive polymer bilayer ionic diode films as dynamic energy-switching carriers. The gradient distribution of ions within the films, excited by moist energy, enables the ionic rectification and further endows the films with electromagnetic energy harvesting capability. In turn, the absorbed electromagnetic energy drives the directional migration of charge carriers and internal ionic current. By rationally regulating the electrolyte and dielectric properties of ionic diodes, it becomes feasible to control targeted electric signals and energy outputs under coupled electromagnetic-moist environment. This work is a step towards enabling enhanced smart interactivities for wirelessly driven flexible electronics.